MATERIALISME VERSUS NILAI-NILAI KONSUMSI ISLAMI: SURVEY PRILAKU KONSUMSI MAHASISWA DI MALANG - Aminullah Achmad Muttaqin; Bintang Nurrizki Dwi Ardianto (STES Islamic Village, 2019)
The purpose of this research is to investigateMuslim student consumer’s behavior. The predictor variablein this study are: materialism and the Islamic values of consumption, on the other hand the target variable is Islamic consumption behavior. Primary data gathered by likert scale questioner survey and for the sample of this research are the students of Islamic Economics program at Universitas Brawijaya Malang. Total of sample are 194 from 372 students of Islamic Economics program (2016-2018). The data had been transformed from ordinal to interval by successive interval. Multiple regression analysis is used in this study. The finding shows that materialism and Islamic values of consumption as significant determinants of Muslim consumer behavior. There is an insignificant negative association between materialism and Muslim Student consumer’s behavior. The finding suggests that most respondents understand and implement Islamic valuesof consumption.